Three-dimensional reconstruction of the membrane skeleton at the plasma membrane interface by electron tomography - Morone, Nobuhiro (The Rockefeller University Press, 2006)
Three-dimensional images of the undercoat structure on the cytoplasmic surface of the upper cell membrane of normal rat kidney fibroblast (NRK) cells and fetal rat skin keratinocytes were reconstructed by electron tomography, with 0.85-nm–thick consecutive sections made ∼100 nm from the cytoplasmic surface using rapidly frozen, deeply etched, platinum-replicated plasma membranes. The membrane skeleton (MSK) primarily consists of actin filaments and associated proteins. The MSK covers the entire cytoplasmic surface and is closely linked to clathrin-coated pits and caveolae. The actin filaments that are closely apposed to the cytoplasmic surface of the plasma membrane (within 10.2 nm) are likely to form the boundaries of the membrane compartments responsible for the temporary confinement of membrane molecules, thus partitioning the plasma membrane with regard to their lateral diffusion. The distribution of the MSK mesh size as determined by electron tomography and that of the compartment size as determined from high speed single-particle tracking of phospholipid diffusion agree well in both cell types, supporting the MSK fence and MSK-anchored protein picket models.